Non-English Majored Students' Attitudes Toward Developing Digital Reading Practices on Online Newspaper Websites - Huu Chanh, Nguyen; Quyen, Chau Thuc (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
The aim of this study is to explore Vietnamese accounting students' attitudes toward using online newspaper websites to develop digital reading practices. Based on Sudiran’s (2015) framework, the research employed a mixed-methods approach by using questionnaire and semi-structured interviews to gather both quantitative and qualitative data. The results indicated that students generally had positive attitudes toward online newspaper websites, particularly regarding their academic benefits, such as improving reading skills and enhancing academic performance. However, students showed varied preferences for usage frequency, with a preference for weekly access rather than daily use. While students acknowledged the role of online newspapers in communication and information retrieval, challenges related to digital literacy and user confidence were highlighted. The study suggests that online newspapers have potential as educational tools but that efforts to improve digital literacy and platform accessibility are needed to increase student engagement. The findings provided valuable insights into the nuanced views of students, which have important implications for both educators and developers seeking to integrate digital tools into learning environments.